TINJAUAN EKONOMI DAN SOSIAL TERHADAP PEMANFAATAN LIMBAH KULIT HEWAN DI INDUSTRI RUMAHAN KERUPUK RAMBAK: STUDI KASUS TRUSMI WETAN, CIREBON - Ridha, Mohammad; Sidik Hidayat, Muhammad; Yana, Enceng; Senja W F, Nurul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to examine the role of the home-based kerupuk rambak industry in Trusmi Wetan Village, Cirebon, as a source of household income and its impact on improving the living standards of the local community. A qualitative approach with a case study method was employed, utilizing in-depth interviews, participatory observations, and documentation of business activities for data collection. Data analysis was conducted interactively through data reduction, presentation, and verification to derive valid conclusions. The findings indicate that this home industry significantly contributes to family income and enhances community welfare. The utilization of animal skin waste in kerupuk rambak production exemplifies a micro-scale circular economy practice that is productive and sustainable. However, the process still generates by-products such as animal hair from skin scraping, which requires further management. These results highlight the potential for developing waste-based enterprises to strengthen local economies and improve quality of life.